2019
DOI: 10.3390/app9235139
|View full text |Cite
|
Sign up to set email alerts
|

Fault Diagnosis of Railway Point Machines Using the Locally Connected Autoencoder

Abstract: Data-driven fault diagnosis is considered a modern technique in Industry 4.0. In the area of urban rail transit, researchers focus on the fault diagnosis of railway point machines as failures of the point machine may cause serious accidents, such as the derailment of a train, leading to significant personnel and property loss. This paper presents a novel data-driven fault diagnosis scheme for railway point machines using current signals. Different from any handcrafted feature extraction approach, the proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…CNN, transfer learning [64] CNN, transfer learning, Bayesian optimization to tune hyperparameters [100] CNN-LSTM [87,103,107] Faster R-CNN [78,88] Faster R-CNN + CNN [73] FastNet, convolutional network-based [120] Fine-grained bilinear CNNs model [70] FCN [119] GAN for CNN [115] Inception-ResNet-v2 & CNN [113] LSTM-RNN [63,71,99] Mask R-CNN…”
Section: Review Of Rail Track Condition Monitoring With Deep Learningmentioning
confidence: 99%
“…CNN, transfer learning [64] CNN, transfer learning, Bayesian optimization to tune hyperparameters [100] CNN-LSTM [87,103,107] Faster R-CNN [78,88] Faster R-CNN + CNN [73] FastNet, convolutional network-based [120] Fine-grained bilinear CNNs model [70] FCN [119] GAN for CNN [115] Inception-ResNet-v2 & CNN [113] LSTM-RNN [63,71,99] Mask R-CNN…”
Section: Review Of Rail Track Condition Monitoring With Deep Learningmentioning
confidence: 99%
“…A hybrid fault diagnosis (HFD) method was adopted to identify a fault based on the current curves of a railway switch machine in [ 8 ]. A locally connected autoencoder was employed to automatically capture high-order features in order to solve the fault diagnosis problem with no training steps based on the current signal of an electric point machine [ 9 ]. DAG-SVMs were applied to intelligently detect a fault after extracting characteristics based on the action current signal of an electric switch machine, and the experiment showed that the accuracy of classification after Kalman filter pretreatment was better than that of direct classification in [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the aforementioned weaknesses, developing a method by which to adaptively learn the features from raw signalizing advanced artificial intelligent techniques would be necessary, instead of extracting and selecting features manually. As a successful DL technology, the autoencoder (AE) with the potential of latent feature extraction has been applied [ 8 , 12 , 34 , 35 ] widely. Compared with traditional feature-extraction methods, AE extracts the deep feature information in the signal more effectively and depends less on prior knowledge or human labor.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional feature-extraction methods, AE extracts the deep feature information in the signal more effectively and depends less on prior knowledge or human labor. Li et al [ 35 ] employed a locally connected autoencoder to automatically capture high-order features. In this work, the current signals are segmented and blended to enhance the temporal characteristic.…”
Section: Introductionmentioning
confidence: 99%